ANALISIS DAN PERANCANGAN CAMPURAN BETON MENGGUNAKAN AGREGAT DARI QUARRY NOEMUTI KABUPATEN TTU - Alokabel, Koilal; Rafael, Jusuf Wilson Meynerd; Suwito, Abdul Syukur Hadi; Lukas, Alva Yuventus (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
The selection of local materials in the manufacture of concrete always sought to be used for the convenience of the manufacturing process and the availability of materials. The local material must refer to the terms and conditions that meet the achievement of the expected concrete quality. In this study, materials originating from the Noemuti Quarry, TTU Regency, namely fine aggregate and coarse aggregate, were used as concrete constituent materials with a planned compressive strength target of 25 MPa. Cylindrical specimens with a diameter of 15 cm and a height of 30 cm were made and treated for testing to the compressive strength of concrete. The results of the material characteristics test showed that the fine and coarse aggregates fulfilled the terms and conditions of concrete constituents. The results of the unit weight test show that the concrete is included in the normal concrete category because the unit weight obtained ranges from 2200 – 2500 kg/m³. The result for the compressive strength test of the concrete, aged 7 days, obtained a compressive strength of 22.65 MPa. For ages 21 days, the compressive strength of concrete is 25.42 MPa, and for ages 28 days, it reaches 26.67 MPa. Thus, the aggregate from the Noemuti Quarry, TTU Regency, both fine and coarse aggregate, is suitable for making normal concrete with a compressive strength of 25 MPa.